Data Encryption for Privacy Protection in Social Apps - Lewis, Daniel (Journal of Computer Science and Software Applications, 2023)
The advent of the big data era has brought the issue of privacy leakage during data release and transmission to the forefront of information security research. Among the prevalent privacy protection techniques are anonymization, data encryption, and differential privacy. This study employs data encryption technology to simulate the development of a social application. The application encrypts user-released information and implements a password protection mechanism. Only individuals with the correct password can access the encrypted data, thereby safeguarding user privacy and preventing the exposure of personal information in textual content and images.